SEMA-JOIN: Joining Semantically-Related Tables Using Big Table Corpora - He, Yeye; Ganjam, Kris; Chu, Xu (International Conference on Very Large Databases (VLDB), 2015)
Join is a powerful operator that combines records from two or more tables, which is of fundamental importance in the field of relational database. However, traditional join processing mostly relies on string equality comparisons. Given the growing demand for adhoc data analysis, we have seen an increasing number of scenarios where the desired join relationship is not equi-join. For example, in a spreadsheet environment, a user may want to join one table with a subject column country-name, with another table with a subject column country-code. Traditional equi-join cannot handle such joins automatically, and the user typically has to manually find an intermediate mapping table in order to perform the desired join. We develop an approach that allows users to perform semantic join automatically, with a click of the button. Our main idea is to utilize a data-driven method that leverages a big table corpus with over 100 million tables to determine statistical correlation between cell values at both row-level and column-level. We use the intuition that the correct join mapping is the one that maximizes aggregate pairwise correlation, to formulate the join prediction problem as an optimization problem. We develop a linear program relaxation and a rounding argument to obtain a 2-approximation algorithm in polynomial time. Our evaluation using both public tables from the Web and proprietary Enterprise tables from a large company shows that the proposed approach can perform automatic semantic joins with high precision in a variety of scenarios. Our benchmark data has been made available on GitHub https://github.com/Yeye-He/Semantic-Join to facilitate future research.